Changes in the Meaning of the Term Ethnos: from the Bible Translations to the New Utopias - Pažėraitė, Aušra Kristina (Religija ir kultūra, 2012)
This article presents an analysis of the genesis of ethnic identity in the contemporary Lithuanian culture. In particular, the definitions of such words as “ethnos”, “ethnicity” are discussed by paying more attention to the fact that these words became common words denoting particular identities of the people only at the beginning of the post-colonial era (nearly synonymous to nation in the Soviet Union and denoting different minorities in the USA, Great Britain, etc.). In the second part of the article, the Biblical (LXX and the MT) words that name different peoples, group identities are compared, their use and the strategy of translation of various texts of the Bible into Lithuanian are analyzed. The article shows how radically the conception and interpretation of the terms that denote various biblical group identities have changed. In the Bible translations into Lithuanian, the word “nation” in the beginning of the 20th century replaced the ancient and more neutral word “people”, which conveyed the Greek word laos, sometimes also ethnos, or the Latin populus. Although the negativity of the term ethnos in its Christian usages can be perceived in the post-soviet Lithuanian culture, a conclusion is made that the traditional explication of the word ethnos in various dictionaries, which stereotypically denotes in LXX pagan people, non-Judeans, non-Christian, is an anachronistic exaggeration. In the final part of the article, certain aspects of post-soviet Lithuanian self-consciousness are discussed by pointing to the self-alienation of this consciousness on the “ethnic” background (Lithuanian nationality is equated to ethnicity, and the concept of ethnicity still preserves a certain negativity of the minority, if not hated, heathen, pagan minority). Finally, certain examples of the attempt to overcome this alienation are presented as the new Utopias, although oriented not toward the future, but back to the past as the attempts to create a new History of Lithuania instead of the present official academic History, which is considered as an essentially alienating one.